Synthesizing and investigating the electrical properties of carbonized metal–organic frameworks - Tran, Huy Quoc; Nguyen, Huong Thi Diem; Nguyen, Hoang Van; Tran, Nhung Thi; Nguyen, Tung Thanh; Ngo, Long Hoang; Tu, Thach Ngoc (Vietnam Journal of Science and Technology, 2024)
The metal–organic frameworks (MOFs)such as VNU-20, ZIF-8, ZIF-67, MOF-199, and MIL-53 were synthesized and carbonized. The obtained MOFs and their carbonized analogs were characterized by powder X-ray diffraction. Subsequently, the carbonized materials were mixed with poly(vinylidene fluoride-co-hexafluoroproplylene)/(1-Methyl-2- Pyrrolidinone) at 5 wt% and cast on glassy carbon electrodes for subsequent analyses. The cyclic voltammetry (CV) measurements of carbonized samples were carried out. The resulting CV scans indicate the reversible CV curves of carbonized VNU-20 electrodes through the reversible redox oxidation reactions between FeII and FeIII. Alongside this, the carbonized VNU-20 is found to have a comparable capacitance with that of carbonized ZIF-67, which is among the highest capacitance materials recorded in the literature for the same class of materials. Although further experiments need to be carried out for the optimization, our analysis initially reveals the promising properties of the carbonized VNU-20 electrode for electro-catalysis and the supercapacitor.